2015
DOI: 10.1016/j.ajhg.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

CODAS Syndrome Is Associated with Mutations of LONP1, Encoding Mitochondrial AAA+ Lon Protease

Abstract: CODAS syndrome is a multi-system developmental disorder characterized by cerebral, ocular, dental, auricular, and skeletal anomalies. Using whole-exome and Sanger sequencing, we identified four LONP1 mutations inherited as homozygous or compound-heterozygous combinations among ten individuals with CODAS syndrome. The individuals come from three different ancestral backgrounds (Amish-Swiss from United States, n = 8; Mennonite-German from Canada, n = 1; mixed European from Canada, n = 1). LONP1 encodes Lon prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
168
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 70 publications
3
168
1
1
Order By: Relevance
“…Homozygous and compound-heterozygous mutations in LONP1 cause cerebral, ocular, dental, auricular, skeletal (CODAS) syndrome, characterized by developmental delay, hearing loss, skeletal defects, and craniofacial anomalies. 20 Although the specific function of SPATA5 is unknown, one possible role for SPATA5 is in mitochondrial integrity and function and would explain the predominant neurological phenotype. It has been suggested that SPATA5 is involved in the morphological transformation of mitochondria from an ''orthodox'' to a ''condensed'' form, which occurs during differentiation in spermatogenesis and might be a mechanism to compensate for the thermodynamically unfavorable conditions and decreased oxygen supply due to the blood-testis barrier for differentiating cells in the adluminal compartment.…”
mentioning
confidence: 99%
“…Homozygous and compound-heterozygous mutations in LONP1 cause cerebral, ocular, dental, auricular, skeletal (CODAS) syndrome, characterized by developmental delay, hearing loss, skeletal defects, and craniofacial anomalies. 20 Although the specific function of SPATA5 is unknown, one possible role for SPATA5 is in mitochondrial integrity and function and would explain the predominant neurological phenotype. It has been suggested that SPATA5 is involved in the morphological transformation of mitochondria from an ''orthodox'' to a ''condensed'' form, which occurs during differentiation in spermatogenesis and might be a mechanism to compensate for the thermodynamically unfavorable conditions and decreased oxygen supply due to the blood-testis barrier for differentiating cells in the adluminal compartment.…”
mentioning
confidence: 99%
“…Lon has been implicated in controlling mitochondrial matrix protein quality, regulating aerobic respiratory function, degrading oxidized proteins, and maintaining mitochondrial DNA (mtDNA) nucleoid integrity (73). Dysfunction of human LONP1 has been associated with ageing, cancer, and CODAS syndrome, a multisystem developmental disorder in humans (73,74). LONP1 has been proposed as an anticancer target (10).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In plants, Lon1 disruption causes changes in mitochondrial respiratory properties, lower protein abundances of oxidative phosphorylation protein complexes (such as Complex I and V), and increases in the abundance of prohibitins and heat shock proteins.…”
Section: Introductionmentioning
confidence: 99%
“…3 Loss of mitochondrial Lon1 leads to reduction in growth rate in yeast and plants and causes developmental disorders and agingrelated diseases in humans. [4][5][6] In plants, Lon1 disruption causes changes in mitochondrial respiratory properties, lower protein abundances of oxidative phosphorylation protein complexes (such as Complex I and V), and increases in the abundance of prohibitins and heat shock proteins. 5 Our recent analysis of a Lon1 loss-of-function line using a progressive 15 N labelling technique to measure protein turnover rates, suggested that Lon1 plays a chaperone role in aiding the proper folding of newly synthesized/imported proteins, particularly in the case of TCA enzymes, and complex I and V subunits.…”
mentioning
confidence: 99%